(untitled) (Applied Biological Research, 2011)
Six parents and their 15 F1’s of brown sarson from a half diallel cross were evaluated for yield and quality traits over two environments to obtain refined estimates of components of genetic variation which get inflated because of G x E confounding at a single location/year. Analysis of variance revealed significant differences among the parents and their crosses for all the traits. The parents CR-1607, CR-1480, KOS-1 and KS-101 were identified as good general combiners for most of the traits. The cross CR-1485 x CR-1607 proved most desirable for seed yield plant-1, 1000-seed weight, primary branches plant-1 and number of seeds siliqua-1. Lines with desirable GCA effects for yield and other attributing traits can be crossed to constitute a base population for subsequent population improvement programmes.